A new species of Egglestonichthys (Teleostei, Gobiiformes, Gobiidae) from Okinawa Island, Japan - Fujiwara, Kyoji (Zookeys, 2020)
Egglestonichthys fulmensp. nov. (Teleostei: Gobiidae) is described on the basis of a single specimen (21.7 mm in standard length) collected from 250 m depth off Okinawa Island, Ryukyu Islands, Japan. The new species is characterized by the following combination of characters: anal-fin rays I, 9; pectoral-fin rays 17, lower rays not free from membrane; longitudinal scale series 25; transverse scales 8; pre-dorsal-fin scale rows 8; cheek and opercle naked; pelvic frenum absent; caudal fin lanceolate, its length 32.2% of SL; interorbital width very narrow, 1.2% of HL (much narrower than pupil diameter); no spicules or odontoid processes on outer surface of gill arches; and body whitish, upper half with broken zigzag pattern of bright yellow patches and associated scattered black melanophores in fresh specimens (melanophores retained in preserved specimens). Several characters, including pectoral-fin ray count, interorbital width, and coloration uniquely distinguish the new species from congeners.